PERBANDINGAN DENYUT NADI ANTARA KELOMPOK YANG MENGGUNAKAN MASKER DAN TIDAK MENGGUNAKAN MASKER SAAT JOGGING - Ahmad Taqiuddin Syam; Ichsani Ichsani; Abdul Rahman (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2022)
This study aims to determine the comparison of the use of masks while jogging to pulse rate. This type of research is a quasi-experimental design. Nonequivalent Control Group Design This design is almost the same as the pretest-posttest control group design, only in this design the experimental group and control group are not chosen randomly. The independent variable in this study was the use of a mask while jogging, while the dependent variable was the pulse rate. The population in this study was the Taman kukui community as many as 22 people, with a total sample of 12 people wearing masks and 12 people not wearing masks. Furthermore, the research data were analyzed using the SPSS 2005 statistical test. The data analysis techniques used were descriptive test, data normality test, t test, homogeneity test, and independent sample t test. Based on the data analysis, the results of the descriptive test with the pulse data of the Taman kukui community before giving the mask obtained an average value (mean) of 84.17, a standard deviation of 11.715, a minimum value of 71, a maximum value of 106. before giving the mask, the value of Kolmogrov Smirnov Z was .200 (P > 0.05). The pulse rate data given by the mask was obtained by the Kolmogorov Smirnov Z value of .200 (P > 0.05). The results of the paired t-test can be obtained a value of sig 0.000 (sig <0.05) with a difference of 125. It is concluded that for the group that does not use a mask, there are also differences in the results of the average pre-test and post-test scores of the group.